2019
DOI: 10.1017/s1041610218002089
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of apolipoprotein E disclosure on healthy Asian older adults: a cohort study

Abstract: Background:The apolipoprotein E (APOE) genotype provides information about Alzheimer’s disease risk, yet genotype disclosure is discouraged due to concerns about possible distress. This is the first study investigating the psychological and behavioral impacts that genetic susceptibility testing for Alzheimer’s disease has in an Asian population.Methods:From March 2016 to November 2017, we ran a prospective cohort study at Duke-National University of Singapore Medical School. 280 healthy Chinese elderly filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Interestingly, 83% indicated that they would prefer to know whether they carried a gene that affected their risk of developing AD. This is in line with other studies surveying preferences for genetic results disclosure in the dementia field 55,56 and supports past studies demonstrating no acute negative psychological consequences of APOE results disclosure 57–59 . Consistent with many clinical studies, we chose not to disclose APOE results to participants.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, 83% indicated that they would prefer to know whether they carried a gene that affected their risk of developing AD. This is in line with other studies surveying preferences for genetic results disclosure in the dementia field 55,56 and supports past studies demonstrating no acute negative psychological consequences of APOE results disclosure 57–59 . Consistent with many clinical studies, we chose not to disclose APOE results to participants.…”
Section: Discussionsupporting
confidence: 83%
“…This is in line with other studies surveying preferences for genetic results disclosure in the dementia field 55,56 and supports past studies demonstrating no acute negative psychological consequences of APOE results disclosure. [57][58][59] Consistent with many clinical studies, we chose not to disclose APOE results to participants. The issue of APOE disclosure is complex and evolving, especially in the context of an online registry, in which it is more difficult to provide access to a genetic counselor or other support system to accurately explain results and their implications.…”
Section: Discussionmentioning
confidence: 99%
“…The first is the Australian study of 133 participants from the Cancer Council registry described above, which also included cancer patients and their family and friends [ 189 ]. The second reported on 280 cognitive healthy, Chinese English-speaking participants in Singapore that had APOE genotype testing [ 194 ]. Assessment using the Beck Anxiety Inventory (BAI) and Centre for Epidemiologic Studies Depression scale (CESD) showed no evidence of APOE genotype disclosure resulting in adverse psychological outcomes [ 194 ].…”
Section: Experiences With Receiving or Returning Resultsmentioning
confidence: 99%
“…The second reported on 280 cognitive healthy, Chinese English-speaking participants in Singapore that had APOE genotype testing [ 194 ]. Assessment using the Beck Anxiety Inventory (BAI) and Centre for Epidemiologic Studies Depression scale (CESD) showed no evidence of APOE genotype disclosure resulting in adverse psychological outcomes [ 194 ]. In addition, they did not identify any significant associations between APOE e4 genotype and behavior changes, such as diet, supplement consumption, and physical or cognitive activity [ 194 ].…”
Section: Experiences With Receiving or Returning Resultsmentioning
confidence: 99%